The Ethics of Asylum Policy: The Case of Iceland - Guðbjörg Lilja Sigurðardóttir 1985- (2010)
Asylum issues have been heavily debated in Europe in recent years and Iceland is no exception to this. The issue of asylum is increasingly complex and asylum seekers are a part of a global migration phenomenon. Iceland represents a special case within the area of asylum policy because of its short immigration history, and geographical position, amongst other factors. A normative analysis of Iceland's asylum policy is carried out by using a combination of ethics and politics. By using the ethical viewpoints of impartiality and partiality, as well as looking at the international refugee regime and at Iceland's background, a nuanced picture can be drawn up of how a state should respond to asylum seekers. The main conclusion is that Iceland needs to develop a comprehensive and coherent asylum policy based on practical achievability and ethical considerations. It is important for Iceland to consider how it can contribute to the international refugee problem in the best way, while at the same time responding to the asylum seekers that reach its borders in an ethically justifiable way.